The neem oil in passion fruit management - Deus, Rafael Mattos [UNESP]; Sampaio, Alosio Costa [UNESP] (Univ Federal Santa Maria, 2015)
Brazil is the largest producer of yellow passion fruit; however declined in production is due to diseases caused by Passion fruit Woodiness Virus (PWV) and Cowpea Aphid-Borne Mosaic Virus (CABMV). Another problems faced by industry are the high water and quality loses and thus, reduce the life of the fruits. The aim of this study was to verify the efficacy of natural neem oil in PWV/CABMV managements, and post-harvest characteristics of fruits and the effect of neem cake on the growth of passion fruits plants. In this study, the yellow passion fruit (Passiflora edulis Sims f. Flavicarpa Deg.) of Afruvec selection, was subjected to fertilization by neem cake and sprayed with neem oil at 0.5%. The vegetative growth, stem diameter, and the incidence of the typical symptoms of PWV/CABMV were evaluated. The effect of neem on the fruits in postharvest was evaluated by water loss, firmness of fruits, and chemical analysis was carried as Brix, pH and Total Titratable Acidity. The results show that neem oil has great potential to control the incidence of virus in passion fruit, due to the action of repellence. The best result was in the group with oil application every 15 days, resulting up to 42% of plants with symptoms at 162 days after planting, whereas 55% to 65% of control plants with symptoms. In growth and post-harvest, neem cake and neem oil showed no significant effects.
Keywords: Organic agriculture; Yellow passion fruit; Neem oil; Neem cake; Sustainability in agriculture